Creative Dramatic Arts Performance: NomNod - Chailangkan, Wilaiwan (Journal of Fine and Applied Arts Khon Kaen University, 2025)
The purposes of this article were to study the background history of the process of making palm sugar and Nom Nod, toddy palm cake, which are the local unique sweets in Phetchaburi Province, and to design the creative dramatic art performance, Nom Nod Dance. The research of the study used the qualitative design method as the study was divided into three steps, 1. data collection, 2. data analysis, and 3. the creation of the performance. The research was conducted under the ethical approval of the human research project at ECPB_R 17/2566, certificate number 34/2566. The study found that the process of making palm sugar and Nom Nod in Ban Rai Krang community, Rai Sathon Sub-district, Ban Lat District, Phetchaburi Province, still preserves the traditional methods. For example, the ingredients that give Nom Nod’s sweet aroma including the properly cooked of toddy palm sugar. An important unique feature of Nom Nod is its wrapping in "I-men" leaves, which emit a pleasant fragrance when heated, combined with the aroma of the dessert ingredients. However, no one has yet created a dance performance based on this dessert. The researcher decided to create a dance performance to serve as a provincial symbol. The primary sources of information included farmers who work with palm sugar and have more than 20 years of experience in making palm sugar and Nom Nod. The process involved collecting data, synthesizing, designing dance moves, and creating a creative dance performance called " Nom Nod." The performance was presented to a committee of experts for critique and refinement.